THU0103 Rebamipide Attenuates Arthritis Severity in Experimental Arthritis Model Via Reciprocal Regulation of Th17–Regulatory T Cells and Mediating Heme Oxygenase-1 Via NRF2 Activation. (23rd January 2014) - Moon, S.-J.; Min, J.-K.; Cho, M.-L.
Abstract : Background: Oxidative stress is thought to underlie the pathophysiology of rheumatoid arthritis (RA). Rebamipide is a gastroprotective agent used for the treatment of gastritis. Several research have showed that rebamipide acts as an oxygen radical scavenger and has an anti-inflammatory property. Objectives: To investigate the in vivo effects of rebamipide in DBA/1J mice with collgen-induced arthritis (CIA), a murine model mimicking human RA. Methods: CIA was induced in DBA/1J mice by intraderma injection of bovine type II collagen. Two weeks later, the mice were given a booster injection of type II collagen. After secondary immunization, rebamipide (0.6 mg/kg and 6 mg/kg) or vehicle (DMSO) was given orally everyday for 4 weeks. We analyzed the samples histomorphologically and used immunohistochemistry to investigate the expressions of nitrotyrosine, tumor necrosis factor-α (TNF-α), inteleukin-1β (IL-1β), IL-6, IL-17, NF-E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1). Spleens isolated from CIA mice were analyzed by confocal analyses using anti-CD4, CD25, Foxp3, IL-17, and STAT3 antibodies. In vitro, Th17 and Treg populations were analyzed by flow cytometric analysis. Results: The arthritis score was lower in CIA mice treated with rebamipide, compared to those treated with vehicle. Histopathologic evidences of joint damage and inflammation were lower in mice treated with rebamipide with a dose-dependent manner, corresponding with a reduction in the expressions of osteoclast and oxidative stress markers. The proportion of Foxp3 + regulatory T cells (Treg) was increased in the spleens of arthritis mice treated with rebamipide, whereas the proportion of Th17 cells was reduced. Rebamipide treatment attenuated in vivo STAT3 activity (both phosphorylated Tyrosine 705 and phosphorylated Serine 727) in CD4 + T cells in spleen. In vitro, rebamipide increased Treg population through Foxp3 up-expression and inhibited Th17 differentiation. The nuclear fraction of murine CD4 + T cells demonstrated enhanced Nrf2 activity following the treatment with rebamipide. Moreover, spleens of rebamipide-treated CIA mice showed markedly enhanced expression of HO-1 expressing cells. Also in human PBMC, rebamipide inhibited Th17 differentiation in human CD4 + T cells, whereas Treg differenation was reciprocally induced. Conclusions: This is the first study to demonstrate the therapeutic effect of rebamipide on an autoimmune arthritis model in mice through reciprocal regulation of Th17 and Treg. The immunoregulatory functions and oxygen radical-scavenging property of rebamipide were associated with activated Nrf2-HO1 signaling. References: Winyard PG et al. Measurement and meaning of markers of reactive species of oxygen, nitrogen and sulfur in healthy human subjects and patients with inflammatory joint disease. Biochem Soc Trans 2011; 39: 1226-1232 Sakurai K et al. Mechanism of hydroxyl radical scavenging by rebamipide: identification of mono-hydroxylated rebamipide as a major reaction product. Free Radic Res 2004; 38: 487-494 Acknowledgements: This study was supported by Daewoong Pharmaceuticals Corporations and by the institute of Clinical Medicine Research of Bucheon St. Mary's Hospital, Research fund, BCMC13YA07. Disclosure of Interest: None Declared